Sakura Development Complex - Pujeda, Maria Jeromia L. (Manila : National University, 2000)
This study shall deal with the development of a community within the global city that will support the needs of these families through providing a complete and sufficient amount of facilities in one city that will help develop their social and mental lives and serve model of every city development through the coming years.
Chapter I. Introduction -- Chapter II. Site analysis -- Chapter III. Research Methods -- Chapter IV. Design framework -- Chapter V. Space programming -- Chapter VI. Estimate -- Chapter VII. Synthesis/ recommendations.
Keywords: COMMUNITY FACILITY; COMPLEX